Constitutional Dilemma: A Misperception of Military’s Tangent Role in Pakistan Politics - Umar, Zahid; Ullah, Saleem (The Lighthouse Journal of Social Sciences, 2022)
Civil Military relations in Pakistan remain a topic of hot debate in Pakistan for a stable government. The military in Pakistan has been malign for intervention in civilian affairs and for dominating the civil government for protecting and securing its interests. In its effort the constitution and rule of law has remained a question for the state of Pakistan. The state of Pakistan has witnessed more often military’s intervention in politics. Hence, its constitutional history becomes largely the imposition and lifting of martial law. Civil military relations will continue to define the future course of the political system and the required amendments in the constitution accordingly. The paper has attempted to highlight the impacts of civil military relations on the constitutional development in Pakistan and future role of political institutions in patronizing these relations in a way to minimize the military intervention in politics and realization of supremacy of the constitution and rule of law in Pakistan. This study has taken into account the theoretical model of separation regarding the civil military relations and added an aspect of personal inclination in coup d’état history of Pakistan. This paper tries to analyze causes that resulted in present imbalance of the power structure and possible ways that can lead to the supremacy of civilian authority and constitution. The paper has focused on the positive role of military as well to quell the impression of military as institution that influence the civilian authority for its own institutional interests.